Strategy Of Illegal Technology Financial Management In Form Of Online Loans - Raden Ani Eko Wahyuni (Jurnal Hukum Prasada, 2020)
The existence of technological development has an impact on aspects of people's economic life. The emergence of financial technology in the form of online loans makes it easy to get the desired funds in a short and easy process. This study aims to discuss the practice of illegal online lending from the perspective of business ethics. The research method used is Normative Juridical with descriptive analytical research specifications. In the practice of Financial Technology (fintech), namely online loans, several problems have been discovered, such as the emergence of illegal online loans, recorded from January 2018 to April 2019, the Financial Services Authority has blocked 947 types of fintech entities in the form of loans between unlicensed online parties. The existence of illegal financial technology can lead to criminal acts such as fraud, money laundering or misuse of consumer's data. This condition was triggered by many people who did not yet know about the technology financial business. Even for legal online loan services that already have risks, the illegal ones will certainly be more risky, and the last many reports from the public as victims of unethical debt collection by online loan service companies. This happens because of the lack of public knowledge about the legality of online loan service companies